Structural Preferences in Phosphanylthiolato Platinum(II) Complexes. Issue 1 (30th July 2015) - Duran, Josep; Polo, Alfonso; Real, Julio; Benet‐Buchholz, Jordi; Solà, Miquel; Poater, Albert
Abstract: The transition‐metal complexes of heterotopic phosphanylthiolato ligands are useful in various reactions which depend on the stereochemistry of the complexes. Bis‐chelate complex [Pt(SCH2 CH2 PPh2 ‐κ 2 P, S )2 ] (1 ) was obtained in good yields by direct base‐free substitution reaction of the corresponding phosphanylthiol (HSCH2 CH2 PPh2 ) with K2 PtCl4 or by oxidative addition of the same phosphanylthiol to Pt(PPh3 )4 . In agreement with the antisymbiosis rule, complex 1 shows a cis ‐P, P arrangement in solid state crystallizing in the monoclinic system ( C 2 /c ). Density functional theory (DFT) calculations on1 reveal the right characteristics for the preferred cis ‐P, P arrangement, rationalizing its formation. Direct base‐free reaction of [PtCl2 (1, 5‐cyclooctadiene)] with one equivalent of the same phosphanylthiol produce the trinuclear complex [PtCl(μ‐SCH2 CH2 PPh2 ‐κ 2 P, S )]3  (2 ) instead of the binuclear structure common in palladium and nickel derivatives. Crystals of2 are triclinic ( P 1 ‾ ) showing a sulfur‐bridging edge‐sharing cyclic trinuclear complex with square‐planar coordination geometry around the platinum atoms and a Pt3 S3 cycle in skew‐boat conformation. This preference for the trinuclear structure was rationalized mechanistically and through conceptual DFT. Abstract : Proving platinum preferences : Transition‐metal complexes of heterotopic phosphanylthiolato ligands are useful in various reactions which depend on the stereochemistry of the complexes. Homoleptic platinum(II) complex with 2‐(diphenylphosphanyl)ethanethiolato ligand shows preference for the cis geometry, while the mixed chlorocomplex shows a sulfur‐bridging edge‐sharing cyclic trinuclear structure.